Thermal boundary condition optimization of ball screw feed drive system based on response surface analysis. (15th April 2019) - Liu, Jialan; Ma, Chi; Wang, Shilong; Wang, Sibao; Yang, Bo; Shi, Hu
Highlights: The thermal boundary conditions of ball screw feed drive system are optimized. The method is extended to predict thermal boundary conditions at different feed rates. The thermal contact resistance is essential for thermal characteristics modeling. Thermal characteristics of the ball-screw feed drive system is analyzed. The thermal deformation of feed drive system is closely related to supporting mode. Abstract: To improve the simulation accuracy of the traditional transient thermal characteristics analysis model (TCAM) of the ball screw feed drive system (BSFDS), the optimization method of the thermal boundary conditions (TBCs), including the thermal loads, the convective heat transfer coefficient and the thermal contact resistance (TCR), was proposed. A multi-objective and multi-parameter optimization model was established based on the hybrid response surface (HRS) and a multi-objective genetic algorithm (MOGA) was developed to optimize the above TBCs. To simulate the thermal characteristics of the BSFDS under different working conditions, the generality of the method was extended to predict the TBCs under different feed rates. To validate the effectiveness of the method, the thermal characteristic experiments of BSFDS were conducted. The results showed that the simulation error for the temperature field was reduced from 25% to 10% and that the simulation error for the thermal elongation was reduced from 30% to 11%.